Pengaplikasian Metode Autoregressive Distributed Lag Dalam Analisis Pengaruh Inflasi Pertumbuhan Ekonomi Dan FDI Terhadap Pengangguran Di Indonesia - Bagas Ade Pangestu; Gabriel Yohannes; Fiqri Perdana Putra (AKUNTANSI 45, 2023)
This study aims to examine the impact of inflation, economic growth, and foreign investment on unemployment rates in Indonesia. The analysis method used is autoregressive distributed lag (ARDL) using time series data from 1991 to 2018 obtained from the World Development Indicators of the World Bank. The research findings indicate that inflation has a significant negative impact in the short term but is not significant in the long term in Indonesia. Economic growth has a significant negative impact on unemployment rates both in the short and long term, while foreign investment also has a significant negative impact on unemployment rates in both the short and long term in Indonesia. Through the ARDL model, this study provides evidence that inflation, economic growth, foreign investment, and unemployment are co-integrated in the long run or move together in the long term. These four variables also exhibit dynamic relationships in the short term, indicating a relatively high speed of adjustment towards equilibrium each year. Based on the research findings, it is recommended that policymakers, particualry the government, create a conducive investment environment by reducing structural barriers in the economy to attract domestic and foreign investments, which, in turn, will stimulate economic growth and create job opportunities in Indonelsia.